Hydrophobic Organic Ammonium Halide Modification toward Highly Efficient and Stable CsPbI2.25Br0.75 Solar Cell. Issue 7 (2nd June 2021) - Duan, Linrui; Wang, Zaiwei; Li, Yanyan; Tan, Liguo; Zhang, Zhuang; Wang, Huanhuan; Yi, Chenyi; Hagfeldt, Anders; Luo, Jingshan
Abstract : Inorganic cesium lead halide perovskite solar cells are promising candidates for next‐generation photovoltaic applications. However, their phase instability and relatively low efficiency hinder their commercialization. Herein, hydrophobic organic ammonium halides (Cl, Br, and I) are rationally used for the modification of inorganic CsPb(I0.75 Br0.25 )3 perovskite solar cells. Benefiting from their passivation effects and hydrophobic long alkyl chain, the modified devices exhibit enhanced efficiency and stability. Among them, the hexadecyltrimethylammonium chloride (CTAC)‐modified device shows the best performance with a power conversion efficiency (PCE) of 18.05%. Furthermore, a gradient triple anion inorganic perovskite CsPb(I0.75 Br0.25 )3− x Cl x layer is formed in situ during the CTAC modification, which demonstrates better phase stability than CsPb(I0.75 Br0.25 )3 . As a result, the modified device also shows excellent stability, maintaining 94% of the initial efficiency after 35 days in N2 atmosphere. Abstract : Hydrophobic organic ammonium halides (Cl, Br, and I) are used for the modification of inorganic CsPb(I0.75 Br0.25 )3 perovskite solar cells. Benefiting from their passivation effects and hydrophobic long alkyl chain, the modified devices exhibit enhanced efficiency and stability. Among them, the hexadecyltrimethylammonium chloride (CTAC)‐modified device shows the best performance with a power conversion efficiency (PCE) of 18.05%.